The estimation of safety booster vaccination children is more senior than 1,5 years against diphtheria, perussis, tetanus, poliomyelitis and Haemophilus influenzae type B with Pentaxim - S. M. Harit; T. V. Tchernyaeva; E. P. Nacharova; G. A. Vasileva; A. A. Ruleva (Журнал инфектологии, 2014)
Supervision over 200 children in the age of 18–42 months (64 healthy and 136 with allergic displays, defeats CNS, often ill, and also having in the anamnesis of reaction to previous introduction DTP or Infanriks), revaccination with Pentaxim. It is shown, that 77% from them had asymptomatic current, only in 1,5% of cases strong reactions with temperature above 38,6°С were observed. Local reactions were marked at 25,5%, essentially more often at children with an allergy, defeat CNS and often ill, than at healthy (7,8%), but did not one child was not adverse events. The estimation safety vaccines Pentaxim confirms expediency of application as 1 revaccination against perussis, diphtheria, tetanus, poliomyelitis and unitary vaccination against Haemophilus influenzae type B in children are more senior than year with a various state of health.